PENINGKATAN PENGETAHUAN PENGGUNAAN BERBAGAI BAHAN TAMBAHAN PANGAN PADA SISWA SMKN 4 BALIKPAPAN - Hutabarat, Michael Alexander; Arista, Yuvita Lira Vesti; Kumalaningrum, Amalia Nur; Manihuruk, Hendrik Vicarlo Saragih; Batubara, Yongki Christandi (UPPM Politeknik Gorontalo, 2024)
The use of Food Additives (BTP) has become increasingly common in food products, especially school snacks. This is a big challenge, where school students need to be educated about Food Additives in the food or drinks they consume, including the types that are allowed and prohibited. Students of SMKN 4 Balikpapan have often consumed snacks containing Food Additives without realizing it. Through this community service program, it is hoped that students' knowledge about Food Additives through socialization and mentoring can increase. This activity includes socialization, interactive discussions, and pre-test and post-test evaluations to measure the effectiveness of the program. It is hoped that after receiving this socialization, students' awareness will increase and can create healthy consumption habit among students.